An efficient gain-flattened C-band Erbium-doped fiber amplifier - Harun, Sulaiman Wadi; Abd Rahman, Faidz; Dimyati, Kaharudin; Ahmad, Harith (IOP Publishing, 2006)
An efficient gain flattened C-band Erbium-doped fibre amplifier is demonstrated using a double-pass configuration wit an IsoGain(TM) Erbium-doped fibre (EDF). The amplifier utilizes a double-propagation of signal provided by an optical circulator at the output end of EDF to obtain an improved flat-gain of 25 dB was obtained from wavelength region from 1528 to 1568 nm. This amplifier has the potential to be used in the high channel count dense wavelength division multiplexing system because of its simplicity and low cost.